Effects of Mo alloying on stability and diffusion of hydrogen in the Nb16H phase: a first-principles investigation. Issue 34 (21st June 2019) - Wang, Dianhui; Wu, Yang; Wan, Zhenzhen; Wang, Feng; Wang, Zhongmin; Hu, Chaohao; Wang, Xiaotian; Zhou, Huaiying
Abstract : First-principles calculations and climbing-image nudged elastic band method were used to investigate the effects of Mo alloying on the structural stability, mechanical properties, and hydrogen-diffusion behavior of Nb. Abstract : First-principles calculations and the method of climbing-image nudged elastic band were used to investigate the effects of Mo alloying on the structural stability, mechanical properties, and hydrogen-diffusion behavior in the Nb16 H phase. The Nb12 Mo4 H phase (26.5 at% Mo) was found to be the most thermodynamically stable structure, with a low Δ H f value (−0.26 eV) and high elastic modulus. Calculations revealed that the tetrahedral interstitial site (TIS) was the predominant location of H in both Nb16 H and Nb12 Mo4 H phases. The calculated H-diffusion energy barrier and the diffusion coefficient of the Nb12 Mo4 H phase were 0.153 eV and 5.65 × 10 −6 cm 2 s −1 (300 K), respectively, which suggest that the addition of Mo would lead to a lower energy barrier and high diffusion coefficients for the Nb16 H phase, thus improving the hydrogen-permeation properties of Nb metal.